Three-dimensional finite element analysis of glass fiber and cast metal posts with different alloys for reconstruction of teeth without ferrule - Verri, Fellippo Ramos [UNESP]; Okumura, Marlice Hayumi Theles [UNESP]; Lemos, Cleidiel Aparecido Araujo [UNESP]; Almeida, Daniel Augusto de Faria; de Souza Batista, Victor Eduardo [UNESP]; Cruz, Ronaldo Silva [UNESP]; Oliveira, Hiskell Francine Fernandes [UNESP]; Pellizzer, Eduardo Piza [UNESP] (Taylor & Francis, 2017)
The aim of this study was to evaluate different materials for restoration of teeth without ferrule by three-dimensional (3D) finite element analysis (FEA). Five models simulating the maxillary central incisor and surrounding bone were simulated according to the type of post: glass fibre post (GFP) or cast metal post (CMP) with different alloys such as gold (Au), silver–palladium (AgPd), copper–aluminum (CuAl) and nickel–chromium (NiCr). Models were designed using Invesalius and Rhinoceros. FEAs were made using FEMAP and NeiNastran, with an applied axial force of 100 N and oblique occlusal load at 45°. Stress distribution among groups was analysed by two-way analysis of variance (ANOVA), followed by post-hoc Tukey’s test. The GFP showed the best stress distribution in the post, followed by CMP with Au, AgPd, CuAl and NiCr alloys, respectively (p <.001). No statistically significant difference in the stress distribution in teeth was found under application of axial load (p >.05). Under oblique load, the GFP generated the highest values of tension among the models, followed by the CMP with NiCr alloy than other models (p <.001). The use of GFP resulted in a lower stress concentration in the post, but increased stress in the tooth without ferrule. The CMP with NiCr alloy exhibited the highest stress distribution among other CMP. To avoid higher stress in teeth, alloys of Au, AgPd and CuAl, respectively, are recommended.
Keywords: dental alloy; finite element analysis; fixed partial dentures; Post and core technique